Bioactivity-guided fractionation of the lipoxygenase and cyclooxygenase inhibiting constituents from Chisocheton polyandrus Merr - Chan, K.Y.; Mohamad, K.; Ooi, A.J.A.; Imiyabir, Z.; Chung, L.Y. (2012)
Lipoxygenase (LOX)-inhibiting compounds from the leaves of Chisocheton polyandrus Merr. were isolated in this study using a bioactivity-guided fractionation technique. Two dammarane triterpenoids, dammara-20,24-dien-3-one (1) (IC50 = 0.69 +/- 0.07 mu M) and 24-hydroxydammara-20,25-dien-3-one (2) (IC50 = 1.11 +/- 0.38 mu M), were isolated and identified based on the soybean LOX assay. Dammara-20,24-dien-3-one (1) exhibited dual inhibition of both human 5-LOX (IC50 = 24.27 +/- 2.92 mu M) and cyclooxygenase-2 (COX-2) (IC50 = 3.17 +/- 0.90 mu M), whereas 24-hydroxydammara-20,25-dien-3-one (2) did not exhibit any significant inhibitory effects. This report is the first to detail the inhibition of LOX and COX by both C. polyandrus and its isolated compounds. (C) 2012 Elsevier B.V. All rights reserved.